Foreign Trade of Nepal: Evidence from Gravity Model - Adhikari, Gyan Mani; Joshi, Binod; Basnet, Bhawana; Chhetri, Santosh (Adhyayan Journal, 2024)
This study employs the gravity model to assess Nepal's trade potential and its relationships with neighboring and significant trading partners. The model, which links trade volume to country size and proximity, forecasts Nepal's trade for 2023 using coefficients derived from the model. By comparing expected trade volume with actual trade, the study determines Nepal's trade potential with 10 key partners. Results showed that while some nations trade above their potential, others trade below it. Notably, Nepal surpasses its trade potential with all 10 partners, including neighboring giants India and China, indicating the strong trading performance of the country.